The Humanistic Side in the Film A Family: Family, Botaiho, and the Struggles of Yakuza Life - Anwar, Fithyani; Putra, Juliadi; Risman, Yunita El (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study explores the humanistic aspects portrayed in Michihito Fujii's film A Family, focusing on the struggles of yakuza members and their families under the restrictions imposed by Japan's Anti-Organized Crime Countermeasures Law (Botaiho). This research employs a descriptive qualitative method and Carl Rogers' humanistic theory to analyze how the characters, particularly Kenji Yamamoto, navigate social stigma while striving to reconstruct their self-identity. Rogers' concept of self-actualization and incongruence provides a crucial framework for understanding Kenji’s psychological struggles and the broader impact of legal and social exclusion. The findings reveal a connection between self-image, self-esteem, and the ideal self in the characters' efforts to reintegrate into society amidst the marginalization effects caused by Botaiho. The film also highlights the broader implications of legal policies on individuals attempting to leave the criminal underworld, underscoring the need for a more inclusive and supportive social structure. This study contributes to discussions on humanistic values and the psychological impact of marginalization while providing insights into legal policies and their social consequences. Thus, it not only enhances our understanding of the individual struggles depicted in the film but also deepens our appreciation of universal human values. Future research could explore comparative studies on former gang members in different cultural contexts to further understand how legal frameworks and societal perceptions influence identity reconstruction and reintegration.Keywords: A Family, film, botaiho, yakuza, humanistic theory